Seasonal variations in performance and asymmetry data for jump and change of direction abilities in female soccer players - Mainer-Pardos, E.; Bishop, C.; Gonzalo-Skok, O. (The Journal of Strength and Conditioning Research, 2024)
The study aimed to evaluate the progression of the percentage-based change of direction (COD) deficit (%CODD) over a competitive season, along with its correlation with performance tests and to examine the impact of the magnitude and direction of asymmetry at 4 stages of the season. Forty-seven (U-16, U-18, and U-20), highly trained, female soccer players performed unilateral vertical jumping (countermovement jump [CMJ]) and horizontal jumping (HJ), 10-m sprint, and 180° change of direction (COD180) tests. The %CODD was also calculated. Significant group and time effects (p < 0.05) were observed in CMJ, HJ, 10-m sprint, and COD180 tests, with U-20 players generally outperforming the U-18 and U-16 groups. Nonsignificant differences were reported in the %CODD between any time point or groups throughout the season. Moderate or large significant (r = 0.44-0.64; p < 0.05) relationships were found between %CODD and 10 m. The direction of asymmetry within and between tests at all time points was slight to moderate (k = -0.29 to 0.57). Notwithstanding, 51% of the players showed the best performance in the horizontal jump with the same leg throughout the season, whereas only 36% in %CODD. This study highlights the importance of developing strategies to improve %CODD depending on the player's position demands. Finally, individually monitoring the magnitude and direction of asymmetry can help practitioners monitor the effects of training and competition throughout the season.